Pattern and Predictors of Maternal Healthcare Services Utilization among Women of Reproductive Age in Lagos, Nigeria - Esther Oluwakemi Oluwole; Alero Ann Roberts; Ifeoma Peace Okafor; Victoria Oluwasola Yesufu (Annals of Global Health)
Background: The world still grapples with alarming maternal mortality rates, particularly in developing nations, including Nigeria. Annual global deaths exceed 500,000, predominantly in developing countries (99%) and sub‑Saharan Africa (over 50%), where the lifetime risk of maternal death is 1 in 26. Millions of women of reproductive age and their children could be saved from poor outcomes through the utilization of available effective affordable maternal healthcare services. Objective: This study assessed the patterns and predictors of maternal healthcare service utilization among women of reproductive age in Lagos state, Nigeria. Methods: A cross-sectional study was conducted among 453 women of reproductive age selected through multistage sampling between July 2022 and March 2023. Data collection employed interviewer-administered questionnaires, and analysis was performed using SPSS V.25 software. Statistical analysis included bivariate and multivariate analyses, with a significance level set at p < 0.05. Findings: Nearly all participants (99%) were familiar with antenatal care (ANC), while 63% knew about postnatal care services, and 82% understood modern family planning methods. Most respondents (86%) accessed ANC in healthcare facilities; however, the majority (70.7%) booked during the second trimester. The majority (97%) attended ANC more than four times, and 77% gave births in healthcare facilities. Notably, 86% attended postnatal care services primarily for child vaccination. Christian religion (adjusted odds ratio (AOR): 1.810; confidence interval (CI): 0.989–3.313), self-employment status of spouses (AOR: 2.949: CI: 1.413–6.153), and household monthly income above 60,000.00 naira (AOR: 2.015; CI: 1.002–4.005) were predictors for ANC use. Similarly, Christian religion (AOR: 2.326; CI: 1.426–3.796), self-employment status of spouses (AOR: 3.111; CI: 1.633–5.929), and having health insurance (AOR: 5.327; CI: 1.229–23.080) were predictors for use of healthcare facilities for childbirth. Conclusion: This study reveals high awareness and utilization of maternal health services but highlights room for improvement in early antenatal care registration and postnatal care beyond the child’s immunization.